High‐altitude adaptation in vertebrates as revealed by mitochondrial genome analyses. Issue 21 (5th October 2021) - Wang, Xibao; Zhou, Shengyang; Wu, Xiaoyang; Wei, Qinguo; Shang, Yongquan; Sun, Guolei; Mei, Xuesong; Dong, Yuehuan; Sha, Weilai; Zhang, Honghai
Abstract: The high‐altitude environment may drive vertebrate evolution in a certain way, and vertebrates living in different altitude environments might have different energy requirements. We hypothesized that the high‐altitude environment might impose different influences on vertebrate mitochondrial genomes (mtDNA). We used selection pressure analyses and PIC (phylogenetic independent contrasts) analysis to detect the evolutionary rate of vertebrate mtDNA protein‐coding genes (PCGs) from different altitudes. The results showed that the ratio of nonsynonymous/synonymous substitutions ( dN/dS ) in the mtDNA PCGs was significantly higher in high‐altitude vertebrates than in low‐altitude vertebrates. The seven rapidly evolving genes were shared by the high‐altitude vertebrates, and only one positive selection gene ( ND5  gene) was detected in the high‐altitude vertebrates. Our results suggest the mtDNA evolutionary rate in high‐altitude vertebrates was higher than in low‐altitude vertebrates as their evolution requires more energy in a high‐altitude environment. Our study demonstrates the high‐altitude environment (low atmospheric O2  levels) drives vertebrate evolution in mtDNA PCGs. Abstract : We studied the influence of different altitudes on the evolution of 104 vertebrate mtDNA PCGs for the first time. Our results demonstrated that the rapid evolution and positive selection sites of mitochondrial genes are one of the important factors for vertebrates to adapt to plateau environment through this research and the high‐altitude environment drove the evolution of vertebrate mtDNA PCGs.